2013
DOI: 10.1634/theoncologist.2013-0072
|View full text |Cite
|
Sign up to set email alerts
|

RAS Mutations in Thyroid Cancer

Abstract: In recent years, our understanding of the genetic alterations underlying thyroid oncogenesis has greatly expanded. The use of molecular markers, including RAS, in the management of thyroid carcinoma is also increasing. This review summarizes the current literature surrounding RAS and discusses its potential as a diagnostic and prognostic indicator in the management of thyroid cancer. The Oncologist 2013;18:926 -932 Implications for Practice: In recent years, our understanding of the molecular mechanisms und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
121
0
8

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(136 citation statements)
references
References 51 publications
7
121
0
8
Order By: Relevance
“…A prospective well-standardized study should provide more accurate information but would need decades to give a good overview of the survival of these patients. x Molecular-biology studies have analyzed the prognostic roles of molecular biomarkers in alterations to the mitogen-activated protein kinase or phosphatidylinositol 3-kinase-AKR T cell lymphoma pathways, or the Telomerase Reverse Transcriptasepromoter mutation [40,41]. However, few studies have reported on the molecular profile of RR disease [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…A prospective well-standardized study should provide more accurate information but would need decades to give a good overview of the survival of these patients. x Molecular-biology studies have analyzed the prognostic roles of molecular biomarkers in alterations to the mitogen-activated protein kinase or phosphatidylinositol 3-kinase-AKR T cell lymphoma pathways, or the Telomerase Reverse Transcriptasepromoter mutation [40,41]. However, few studies have reported on the molecular profile of RR disease [42,43].…”
Section: Discussionmentioning
confidence: 99%
“…Other molecular alterations, i.e. point mutation in the three RAS genes (H, K, and N), have also been implicated in the pathogenesis of thyroid carcinomas, but their specificity is lower than that of the previously mentioned markers, as these mutations have also been identified in quite a high percentage of FA (25). Among these mutations, codon 61 of the NRAS gene is the most frequently mutated site, and seems to be also associated with distant metastases (26,27).…”
Section: Molecular Testingmentioning
confidence: 99%
“…RAS mutations are more prevalent and seem to be more relevant as a prognostic indicator in follicular patterned lesions (FVPTC, FTC and, namely, PDTC) than in cPTC (18). All of the three RAS genes (H, K and N-RAS) were shown to be mutated in both benign and malignant thyroid tumours but the frequency of the mutations is higher in FTC (36%), PDTC (55%) and UTC (52%) and more frequently affects the N-RAS gene (20).…”
Section: Ras Mutations and Prognosismentioning
confidence: 96%
“…RAS mutations are less prevalent in benign and malignant Hürthle cell tumours (5 and 11% respectively) than in their non-Hürthle cell counterparts and less prevalent in PTC (10%) than in FTC (25-30%) (7,20). Within PTC, RAS mutations are rare in its classic form, whereas in FVPTC, its prevalence falls within the range of other follicular patterned tumours (w25%) (6).…”
Section: Ras Mutations and Prognosismentioning
confidence: 98%